Strategic Positioning Of Islamic Banks In Constructing Brand Image To Strengthen Brand Equity - Dadang, Agus (Equity: Jurnal Ekonomi, 2025)
Islamic banking in Indonesia has significant potential, supported by a large Muslim population and a strong regulatory framework. However, its market share remains stagnant compared to international benchmarks such as Malaysia and Saudi Arabia. This study aims to examine positioning strategies of Islamic banks in strengthening brand image to improve brand equity and to identify factors behind their limited growth. Using a descriptive qualitative approach, the research draws on literature reviews and secondary data from the Financial Services Authority, Bank Indonesia, and academic sources between 2019–2024. The findings reveal that the market share target of 20% in the Sharia Banking Roadmap 2020–2025 has not been met, with actual achievement only 7.72% in 2024. The shortfall is driven by weak product differentiation—for example, financing schemes and savings products that closely resemble conventional banks—along with underdeveloped digital platforms, relatively high financing margins, and low public awareness of sharia-based values. Compared with Malaysia’s emphasis on digital innovation and Saudi Arabia’s integration of Islamic banking into national identity, Indonesia still relies heavily on “riba-free” narratives. This study contributes by integrating positioning, brand image, and brand equity analysis while drawing international lessons. The implications highlight the need for halal lifestyle positioning, digital service transformation, and cross-sector collaboration to build stronger brand equity and accelerate market growth.